TINJAUAN YURIDIS TINDAK PIDANA PENELANTARAN RUMAH TANGGA - Widya Oktaviani H, Musa Darwin Pane (Fakultas Hukum Universitas Komputer Indonesia, 2021)
ABSTRACT This study aims to determine the law enforcement of neglected household defendants who have paid mut'ah and iddah livelihoods so as to identify legal certainty for the defendant. As for the background of this writing because there is no legal regulation concerning living that leads to neglect of the household so that legal certainty has not been created in the case of a crime of neglect of the household. This research is analytical descriptive research, and uses a normative juridical approach. The type of data used is secondary data, the source of the data obtained through literature study, legislation, the decision of the Judge of the Cianjur District Court and the Bandung High Court. Data collection techniques used are primary data in the form of documentation and secondary data which is library research. Based on this research, the results are obtained that, mut'ah and iddah are part of